1995
DOI: 10.2172/125115
|View full text |Cite
|
Sign up to set email alerts
|

Radiological characterization of spent control rod assemblies

Abstract: Portions of this document may be illegible electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…A variety of 36 Cl analysis methods have been described in the literature, based on ion exchange chromatography [1], silver salts precipitation [1,2] or elimination of iodine by extraction in an ammoniacal solution and silver salts precipitation [3] using a liquid scintillation spectrometer, a gas proportional counter [4] or accelerator mass spectrometry [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of 36 Cl analysis methods have been described in the literature, based on ion exchange chromatography [1], silver salts precipitation [1,2] or elimination of iodine by extraction in an ammoniacal solution and silver salts precipitation [3] using a liquid scintillation spectrometer, a gas proportional counter [4] or accelerator mass spectrometry [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Lepel et al showed that spent control rods from PWRs can reach up to 1 GBq/g HM 108m Ag and 90 MBq/g HM 110m Ag at the upper part of the control rods with a 108m Ag/ 110m Ag activity ratio of >10. 38 The 108m Ag activity even exceeds the 60 Co activity from steel components in the spent Ag−In−Cd control rods by more than 1 order of magnitude. 38 The significant differences in the 108m Ag/ 110m Ag isotopic ratio are a potentially useful forensic indicator that may provide information about the exact origin of the reactor-derived radiosilver upon its release into the environment.…”
mentioning
confidence: 99%
“…38 The 108m Ag activity even exceeds the 60 Co activity from steel components in the spent Ag−In−Cd control rods by more than 1 order of magnitude. 38 The significant differences in the 108m Ag/ 110m Ag isotopic ratio are a potentially useful forensic indicator that may provide information about the exact origin of the reactor-derived radiosilver upon its release into the environment.…”
mentioning
confidence: 99%
“…Não obstante apresentar atividade pequena em relação à atividade total dos rejeitos radioativos, a determinação precisa de 108m Ag é considerada importante para o gerenciamento adequado desses rejeitos (Lepel et al, 1995;Bihari et al, 2010).…”
Section: Determinação De 108m Agunclassified
“…A diferença entre os resultados obtidos para os reatores BWR e PWR é atribuída ao fato da fonte principal dos radionuclídeos desses pares RDM/RC em reatores PWR ser os tubos do gerador de vapor (Raymond et al, 1995), enquanto em reatores BWR (que não possuem gerador de vapor) o revestimento de aço inoxidável das barras de controle feitas de carbeto de boro (B 4 C) (Lepel et al, 1995) (Silva et al, 2002), durante as quais se observou descamação e pites de corrosão crescentes no revestimento de Ni dessas barras (Silva et al, 2002). Tais descontinuidades no revestimento de Ni causaram a liberação progressiva de isótopos radioativos de Ag das barras de controle para a água de refrigeração, o que foi constatado na época pela detecção de 110m Ag em diversas medidas por espectrometria de raios-gama realizadas na piscina do reator IEA-R1 (Terremoto et al, 2000;Terremoto et al, 2002;Zeituni et al, 2004a;Zeituni et al, 2004b).…”
Section: Comparação Com Concentrações De Atividade Naturaisunclassified